1998
DOI: 10.1523/jneurosci.18-13-04929.1998
|View full text |Cite
|
Sign up to set email alerts
|

Neurturin Exerts Potent Actions on Survival and Function of Midbrain Dopaminergic Neurons

Abstract: Glial cell line-derived neurotrophic factor (GDNF) exhibits potent effects on survival and function of midbrain dopaminergic (DA) neurons in a variety of models. Although other growth factors expressed in the vicinity of developing DA neurons have been reported to support survival of DA neurons in vitro, to date none of these factors duplicate the potent and selective actions of GDNF in vivo. We report here that neurturin (NTN), a homolog of GDNF, is expressed in the nigrostriatal system, and that NTN exerts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
193
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(211 citation statements)
references
References 25 publications
14
193
1
Order By: Relevance
“…In addition, another possibility is to suggest that further functional recovery of lesioned nigrostriatal pathways is not obtained by GDNF alone, and that other neurotrophic factors such as neurturin or artemin, another member of GDNF family with strong homology to GDNF, may be necessary. [35][36][37] In conclusion, we have shown that (1) AAV vectormediated GDNF gene delivery in the striatum promoted the survival of DA neurons in the SN, increased the density of TH-IR fibers, and ameliorated behavioral and biochemical deficits even after the degenerative process had begun; (2) GDNFflag fusion protein was detected in the SN, suggesting the transgene-derived GDNF was retrogradely transported from the striatum to DA cell bodies in the SN, while maintaining functional connections within the nigrostriatal pathway. These data indicate that AAV-mediated GDNF gene delivery in the striatum is feasible as a neuroprotective gene therapy of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another possibility is to suggest that further functional recovery of lesioned nigrostriatal pathways is not obtained by GDNF alone, and that other neurotrophic factors such as neurturin or artemin, another member of GDNF family with strong homology to GDNF, may be necessary. [35][36][37] In conclusion, we have shown that (1) AAV vectormediated GDNF gene delivery in the striatum promoted the survival of DA neurons in the SN, increased the density of TH-IR fibers, and ameliorated behavioral and biochemical deficits even after the degenerative process had begun; (2) GDNFflag fusion protein was detected in the SN, suggesting the transgene-derived GDNF was retrogradely transported from the striatum to DA cell bodies in the SN, while maintaining functional connections within the nigrostriatal pathway. These data indicate that AAV-mediated GDNF gene delivery in the striatum is feasible as a neuroprotective gene therapy of PD.…”
Section: Discussionmentioning
confidence: 99%
“…It was found to promote the survival of developing and mature dopaminergic neurones in vitro, These effects were similar in strength to those of GDNF [79,80]. Neurturin is expressed in the ventral midbrain and striatum during development [80].…”
Section: Effects Of Neurturin In Vitromentioning
confidence: 71%
“…Neurturin has been found to exert protective and functional effects on dopaminergic nigrostriatal neurones after 6-OHDA lesions of the adult rat MFB [79,80] or striatum [81,82] and after axotomy of the adult rat MFB [83]. The study by Rosenblad and colleagues directly compared the effects of neurturin with those of GDNF in the striatal 6-OHDA lesion model.…”
Section: Effects Of Neurturin In Vivomentioning
confidence: 99%
“…46 Neurturin has been shown to enhance survival of dopaminergic neurons both in vitro, and in rodent and monkey models of PD. [47][48][49][50][51][52][53] Evidence for restoration has also been found in rodents treated with 6-OHDA 52 and in aged monkeys, in which there is an age-related loss of dopaminergic phenotype. 54 In the later studies, an adenoassociated type 2 viral vector that encoded for human NRTN was injected unilaterally into the striatum of the aged rhesus monkeys.…”
Section: Neurturinmentioning
confidence: 90%